Expression and purification of Tick-borne encephalitis virus Capsid protein - Schmelzer, Jakob (Jihočeská univerzita, 2023)
Tick-borne encephalitis virus (TBEV) is an important pathogen of the family Flaviviridae with an emerging health concern. Virus causes severe neurological disorders to human population in Europa and Asia. Despite effective vaccine, there is no specific antiviral treatment till now. The capsid protein encapsules the viral positive-sense single-stranded RNA and is essential in packaging and assembling of new virions within the host. A deeper understanding of these interactions and their implications should lead to new antiviral strategies and drug design. This thesis deals with the expression and purification of the capsid protein without membrane anchor using Escherichia coli expression system.
Expression and purification of Tick-borne encephalitis virus Capsid protein
Keywords: Flavivirus; Tick-borne encephalitis virus; Capsid protein; Cloning; Expression; IPTG; BL21-CodonPlus (DE3)-RIPL; Immobilized Metal Affinity Chromatography; Flavivirus; Tick-borne encephalitis virus; Capsid protein; Cloning; Expression; IPTG; BL21-CodonPlus (DE3)-RIPL; Immobilized Metal Affinity Chromatography